The effect of age on blood pressure response by 4‐week treatment perindopril: A pooled sex‐specific analysis of the EUROPA, PROGRESS, and ADVANCE trials - Michelle M. Schreuder; Katrina M. Mirabito Colafella; Eric Boersma; Jasper J. Brugts; Jeanine E. Roeters van Lennep; Jorie Versmissen (Wiley, 2021)
Abstract Previous studies showed that postmenopausal women are more likely to have poorly controlled hypertension than men of the same age. Whether this is caused by inadequate treatment or poor response to antihypertensive agents remains unknown. The aim of this study is to analyze treatment response to the most potent renin angiotensin aldosterone system (RAAS) inhibitor perindopril in different age categories in women and men. Individual patient data were used from the combined European Trial on Reduction of Cardiac Events With Perindopril (EUROPA), Perindopril Protection Against Recurrent Stroke Study (PROGRESS), and Action in Diabetes and Vascular disease: Preterax and Diamicron‐MR Controlled Evaluation (ADVANCE) trials, which include patients with vascular disease (n = 29,463). We studied the relative and absolute changes in systolic blood pressure (SBP) and diastolic blood pressure (DBP) during a 4‐week run‐in phase in which all patients were treated with the perindopril‐based treatment in different age categories. In total, 8366 women and 21,097 men were included in the analysis. Women greater than 65 years of age showed a significantly smaller blood pressure reduction after perindopril treatment (2.8 mmHg [95% confidence interval CI = 0.1-5.5] less reduction compared to women ≤45 years, p = 0.039). In men, the SBP reduction after perindopril in patients greater than 55-65 and greater than 65 years was lower compared to the age category less than or equal to 45 years (adjusted mean difference >55-65: 2.8 mmHg [95% CI = 1.8-3.7], p < 0.001, >65: 3.7 mmHg [95% CI = 2.7-4.7], p < 0.001). A trend of less blood pressure reduction was seen with ageing in both men and women (p < 0.001). To conclude, we observed that in both women and men the perindopril leads to less SBP reduction with increasing age, whereas the DBP reduction increases with age. More research is needed to determine whether it would be beneficial to use age‐adjusted perindopril dosages.